El filicidio en España: situación y limitaciones para su estudio = Filicide in Spain : situation and limitations of its study - Picazo, Irene Barón (Behavior & Law Journal, 2021)
The term filicide is used to refer to the death of a child at the hands of a parent. It is a type of homicide with a low prevalence worldwide, which makes it difficult, in part, to study. In addition, the indiscriminate use of different names for the same phenomenon, as well as the different definitions of what a filicide is, make it difficult to quantify, compare and study this phenomenon. Moreover, this criminal phenomenon has been little studied in Spain, so here we will present the results of an empirical study of a sample of 35 cases involving 40 victims and 39 perpetrators of filicide. The cases correspond to homicides solved by the National Police and the Civil Guard between 2010 and 2012. The analyses highlight the incidence of female perpetrators and underage victims in this type of homicide, as well as the existence of mental disorders and suicidal behaviour on the part of the perpetrators. It is also noteworthy that female perpetrators tend to have younger victims, and tend to be more likely to have a mental disorder, although it is men who commit suicide after the fact. These findings are discussed in relation to previous national and international work.